Belonging to a peer support group enhance the quality of life and adherence rate in patients affected by breast cancer: A non-randomized controlled clinical trialFNx01 - Afsaneh Malekpour Tehrani; Ziba Farajzadegan; Fariborz Mokarian Rajabi; Ahmad Reza Zamani (Journal of Research in Medical Sciences, 2011)
Background: Breast cancer is the most common cancer in women. It seems that breast cancer patients benefit from meeting someone who had a similar experience. This study evaluated the effect of two kinds of interventions (peer support and educational program) on quality of life in breast cancer patients. Methods: This study was a controlled clinical trial on women with non-metastatic breast cancer. The patients studied in two experimental and control groups. Experimental group took part in peer support program and control group passed a routine educational program during 3 months. The authors administered SF-36 for evaluating the quality of life pre-and post intervention. Also, patient′s adherence was assessed by means of a simple checklist. Results: Two groups were similar with respect of age, age of onset of the disease, duration of having breast cancer, marital status, type of the treatment receiving now, and type of the received surgery. In the control group, there were statistically significant improvements in body pain, role-physical, role-emotional and social functioning. In experimental group, role-physical, vitality, social functioning, role-emotional and mental health showed significant improvement. Vitality score and mental health score in experimental group was significantly higher than that of the control group, both with p < 0.001. Also, it was shown that adherence was in high levels in both groups and no significant difference was seen after the study was done. Conclusions: According to the results of this study, supporting the patients with breast cancer by forming peer groups or by means of educational sessions could improve their life qualities.